FundSphere: The Ultimate Mobile App for Seamless Group Fund Management - Dr Pavithra M; Sajith G; Prakash S; Sowbarnika M (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
FundSphere is a mobile application designed to streamline and enhance group fund management by providing a structured, efficient, and transparent financial tracking system. Managing shared financial resources in groups often leads to challenges such as mismanagement, lack of accountability, and inefficient tracking. FundSphere addresses these issues by offering real-time balance updates, automated contribution tracking, and timely notifications. Additionally, the application ensures data security through robust authentication protocols. Unlike conventional methods that rely on spreadsheets, manual ledgers, or expense-sharing applications, FundSphere introduces an intelligent and automated financial tracking mechanism tailored specifically for collaborative group fund management. This paper explores the existing challenges in group fund management, evaluates the limitations of current solutions, and presents FundSphere as an innovative, scalable, and structured alternative. Furthermore, it highlights the implementation methodology, security measures, and potential future advancements, ensuring the sustainability and reliability of the platform.